2011
DOI: 10.3892/ijo.2011.924
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α is a novel target of miR-19a

Abstract: Abstract. Many studies have demonstrated the overexpression and amplification of the miR-17-92 cluster in malignant human cancers, including B-cell lymphomas and lung cancers. The purpose of this study was to investigate for the first time, the expression of the miR-17-92 cluster in esophageal squamous cell carcinoma (ESCC). The miR-17-92 cluster was found to be overexpressed in 21 out of 28 (75%) esophageal cancer samples. It was also found that overexpression of the miR-17-92 cluster could promote cellular g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 24 publications
4
38
0
Order By: Relevance
“…This suggested that miR-19a was essential for TNF-α-mediated EMT and provided mechanistic insight into the role of miR-19a in mediating some of the TNF-α mediated EMT activity. Considering, TNF-α has been reported previously to be a miR-19a gene target in ESCC34 and ulcerative colitis35, we had conducted the western blot assay to determine whether TNF-α would be a target in CRC cells. Ectopic miR-19a expression decreased the expression of TNF-α in both HCT 116 and Caco-2 cells (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that miR-19a was essential for TNF-α-mediated EMT and provided mechanistic insight into the role of miR-19a in mediating some of the TNF-α mediated EMT activity. Considering, TNF-α has been reported previously to be a miR-19a gene target in ESCC34 and ulcerative colitis35, we had conducted the western blot assay to determine whether TNF-α would be a target in CRC cells. Ectopic miR-19a expression decreased the expression of TNF-α in both HCT 116 and Caco-2 cells (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-19b is one of the major members of the miRNA-17-92 family (8). It has been found that miR-19b is highly expressed in breast, cervical, colon and pancreatic carcinomas and participates in the apoptosis of tumor cells (9,10). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found 2 members ( miR-17-5p , miR-20a ) of miR-17-92 cluster only appeared in the subtype 1. MiR-17-92 cluster which locates on the C13orf25 gene is overexpressed in ESCC and usually promote cancer cell proliferation [38]. Then we validated the expression of these two clusters in an independent data set (detail in Methods), and found miR-17-5p , miR-20a and miR-16-5p were upregulated in ESCC.…”
Section: Resultsmentioning
confidence: 99%